The road to cervical cancer elimination in Malaysia: Evaluation of the impact and cost‐effectiveness of human papillomavirus screening with self‐collection and digital registry support. Issue 12 (25th August 2021) - Keane, Adam; Ng, Chiu Wan; Simms, Kate T.; Nguyen, Diep; Woo, Yin Ling; Saville, Marion; Canfell, Karen
Abstract: The WHO has launched a global strategy to eliminate cervical cancer through the scale‐up of human papillomavirus (HPV) vaccination, cervical screening, and cervical cancer treatment. Malaysia has achieved high‐coverage HPV vaccination since 2010, but coverage of the existing cytology‐based program remains low. Pilot studies found HPV self‐sampling was acceptable and effective, with high follow‐up rates when a digital registry was used, and recently the Malaysian Government announced plans for a national HPV‐based screening program. We therefore evaluated the impact of primary HPV screening with self‐collection in Malaysia in the context of Malaysia's existing vaccination program. We used the " Policy1‐Cervix " modeling platform to assess health outcomes, cost‐effectiveness, resource use and cervical cancer elimination timing (the year when cervical cancer rates reach four cases per 100 000 women) of implementing primary HPV testing with self‐collection, assuming 70% routine‐screening coverage could be achieved. Based on available data, we assumed that compliance with follow‐up was 90% when a digital registry was used, but that compliance with follow‐up would be 50‐75% without the use of a digital registry. We found that the current vaccination program would prevent 27 000 to 32 200 cervical cancer cases and 11 700 to 14 000 deaths by 2070. HPV testing with a digital registry was cost‐effective (CER = US 6953‐7549 < US 11 373[<1×GDP per capita]) and could prevent an additional 15 900 to 17 800 cases and 9700 to 10 600 deaths by 2070, expediting national elimination by 11 to 20 years, to 2055 to 2059. If HPV screening were implemented without a digital registry, there would be 1800 to 4900 fewer deaths averted by 2070 and the program would be less cost‐effective. These results underline the importance of HPV testing as a key elimination pillar in Malaysia.